Investigating the Indonesian Translation of the U.S. Embassy Press Release - Maharsi, Ista (Journal of English and Education (JEE), 2009)
Translating formal text that may contain social, political, and crucial issues that involve many parties and possibly pose reactions across countries does not seem to be a simple task to complete. Due to diverse reactions of readers from different languages, a translator needs to be very careful to transfer meanings and the emotion within a text. Translation strategies, language use, types of text, genre, discourse and values are urgent issues to reconsider during the translation process. This paper investigates the translation strategies implemented in the Indonesian translation of the U.S. Embassy Press Release in response to Newsweek's Report on Alleged Desecration of the Holy Qur'an from the point of views of text, genre, and discourse as proposed by Hatim and Munday. In addition, several alternative translations are also offered to show different impacts of a translated text. Despite many translation methods that are used in doing the translation process, a text still bear its own genre, discourse and therefore stands in its own identity while at the same time the target text should keep voicing at least similar values and bring about similar impacts on readers.